Mitigation of Polycyclic Aromatic Hydrocarbons Formation in Goat Satay by Shallots Juices Marination - E. Saputro; L. E. Radiati; W. Warsito; D. Rosyidi (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study aimed to mitigate the carcinogen formation of polycyclic aromatic hydrocarbons (PAHs) in charcoal-grilled goat satay by marinating raw goat-satay with shallots (Allium cepa var. Ascalonicum) juices. The experiment used a 2 x 4 split-plot factorial randomized block design. The experiment consisted of 2 treatments of 2 goat satay types (without and with sliced fat) and 4 treatments of marination with shallots juice at concentrations of 0%, 10%, 20%, and 30% (gmL-1 of fresh shallots in distilled water) for 60 minutes at 4 °C. A total of 24 samples of raw and grilled goat-satay were used for 3 replication groups. The marination with 10% and 20% shallots juices significantly reduced the BaP and BaA until they were not detected even though they increased the non-carcinogenic Pyr levels in the grilled goat-satay with and without sliced fat. The marination with 10%, 20%, and 30% shallots juice significantly prevented the formation of Phe, Ace, and Nap so that they were not detected in the grilled goat-satay with and without sliced fat. The marination with 30% shallots juice of raw goat-satay without sliced fat resulted in the highest antioxidant activities and detectable BaP levels (3.88 mg kg-1).